Kindred spirits = shilombish ittibachvffa - Widener, Leslie Stall (Racial justice in America: Indigenous peoples., 2024)
"Ireland, Choctaw Nation, Navajo Nation, and Hopi Nation: linked forever through generosity and care over almost two centuries from the Potato Famine to the Covid pandemic"--